Glocal Dialogue Transformation through Transcultural Communication - Kazuma Matoba (Fondazione Eni Enrico Mattei (FEEM), 2003)
This paper addresses the role of dialogical communication in acculturation efforts within organizations and regions, especially during periods of transition, mergers, technological innovations, and globalization. This optimal communication mode can be achieved through a dialogue process proposed by David Bohm and developed by Peter Sense at MIT, Boston. The dialogue process, as an integral part of intercultural communication training, aims at promoting dialogue competence for intercultural communication in which man can learn how to better deal with their own stereotypes of other cultures and eventually acquire a generally de-stereotyping style of communication. It has tried out in a small city in Germany, since April 2002. About 25 citizens of the city are taking part in this dialogue process. The empirical part of this study tries to describe the socio-psychological transformation of the dialogue-group.
Keywords: Z10; 330; Dialogical communication; Transcultural communication; Acculturation process; Sociopsychological transformation